Implication of Traditional Ecological Knowledge on Forest Resource Management - Laudari, Dhruba (Himalayan Journal of Sociology and Anthropology, 2011)
The primary approaches within contemporary ecological anthropology are cultural ecology, historical ecology, political ecology and spiritual ecology. The cumulative approach developed on by fusing these approaches is applied dimension of ecological anthropology known as environmental anthropology. Human populations have ongoing contact and impact upon the land, climate, plant and animal species in their vicinities and these elements of their environment have reciprocal impacts on humans. The theme of traditional ecological knowledge is important for the consideration of a broad range of question related to nature-environment relations. Different groups of people in various parts of the world perceive and interact with nature differently, and have different traditions of environmental knowledge. Their perceptions and knowledge are partly shaped by their values, worldview and environmental ethics. In the exploration of environmental ethics and religion toward an ecologically sustainable society, indigenous peoples and traditional ecological knowledge have attracted considerable attention from both scholars and popular movements. The lesson from this ield study, under the theoretical outline of cultural and human ecology includes the importance of cultural conservation of forest resources, adaptive management, uses of traditional ecological knowledge and development of religious/spiritual conservation ethic. This may contribute to the development of an interdisciplinary conservation science with a more sophisticated understanding of social-ecological interactions. The indings thus could be used for formulating better policies for sustainable management of forest/natural resources. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4669 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 77-90